Excessive DAO inhibits myoblast migration, leading to impaired myotube fusion and muscle strength decline by reducing ECM - Liu, Xiang; Xue, Jianchao; Liang, Yiming; Li, Zhenggang; Xu, Rui; Yang, Huaimei; Zhao, Yu; Wang, Qiyang; Hou, Jianhong; Lu, Sheng (Frontiers in Bioengineering and Biotechnology, 2025)
IntroductionThe molecular mechanisms underlying muscle strength decline, particularly in age-related conditions such as sarcopenia, remain poorly understood. Previous omics studies have suggested a potential association between AOC1 (encoding diamine oxidase, DAO, mainly expressed in intestine) and muscle weakness, but experimental validation and mechanistic insights are lacking. This study aims to investigate the influence of secretory DAO on muscle function and its potential receptors.MethodsSerum DAO levels were measured in elderly participants (n = 129) using ELISA and correlated with grip strength. Animal models included naturally aging C57 mice, rapidly aging SAMP8 mice, and a glycerol-induced acute muscle injury model were established to verify the role and content of DAO under overall condition. In vitro studies used C2C12 myoblasts treated with recombinant human DAO to assess migration, fusion, and cytotoxicity. Mechanistic insights were explored via mass spectrometry, co-immunoprecipitation, Western blotting, and immunofluorescence.ResultsElderly males with low grip strength exhibited significantly higher serum DAO levels, while no such correlation was observed in females. Aged and injured mouse models showed elevated DAO content in skeletal muscle, accompanied by fast-twitch fiber loss. In C2C12 cells, adding DAO recombinant protein inhibited myoblast migration and fusion without affecting viability. Mechanistically, DAO bound to Fbln1, suppressed FAK phosphorylation (Y576/Y577), and disrupted cytoskeletal remodeling.DiscussionThis study provides experimental evidence that exssive DAO impairs muscle strength by inhibiting myoblast migration and fusion via the Fbln1/FAK pathway. The findings reveal a potential regulation between different organs and cells, and highlight a novel metabolic-biomechanical uncoupling mechanism linked by DAO in sarcopenia.